2014
DOI: 10.2139/ssrn.2433597
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Bubble in the Art Market?

Abstract: Abstract:The record-breaking prices observed in the art market for the last three years have rais the question of whether we are experiencing a speculative bubble. Given the difficulty to determine the fundamental value of artworks, we apply a right-tailed unit root test with forward recursive regressions (SADF test) to detect explosive behaviors directly in the time series of four different art market segments ("Impressionist and Modern", "Post-war and Contemporary", "American", and "Latin American") for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
(9 reference statements)
1
13
0
4
Order By: Relevance
“…The best returns are presented in the 0.75 quantile, which means that prices of the most expensive paintings have gone up significantly. In this case the most attractive sector is postwar art market because it has the highest value of the average price index and lower dispersion of the index comparing with the contemporary art which is the most speculative sector as we can see (however [23] argue that all segments -"Impressionist and Modern", "Post-war and Contemporary", "American" and "Old Masters" -are likely to demonstrate the speculative behaviors, if they are compared with other markets). The art of old masters along with impressionism is not very interesting for investors.…”
Section: Resultsmentioning
confidence: 80%
“…The best returns are presented in the 0.75 quantile, which means that prices of the most expensive paintings have gone up significantly. In this case the most attractive sector is postwar art market because it has the highest value of the average price index and lower dispersion of the index comparing with the contemporary art which is the most speculative sector as we can see (however [23] argue that all segments -"Impressionist and Modern", "Post-war and Contemporary", "American" and "Old Masters" -are likely to demonstrate the speculative behaviors, if they are compared with other markets). The art of old masters along with impressionism is not very interesting for investors.…”
Section: Resultsmentioning
confidence: 80%
“…This emotional aspect is shown to affect prices of collectibles (see Renneboog and Spaenjers, 2013), and can lead to speculative bubbles (e.g. Penasse and Renneboog, 2017;Kräussl, Lehnert and Martelin, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The concept brings together the social and behavioral underpinnings of the art market, different from existing studies on the art market bubbles that focus on the speculative bubble revealed in the price of artworks fetched in the contemporary auctions (c.f. Kräussl et al 2016). 15 A social bubble is defined as "strong social interactions between enthusiastic supporters weave a network of reinforcing feedbacks that lead to widespread endorsement and extraordinary commitment by those involved, beyond what would be rationalized by a standard cost-benefit analysis in the presence of extraordinary uncertainties and risks."…”
Section: Art Market As a "Social Bubble"mentioning
confidence: 99%